Accounting and analytical support for settlements with company counterparties - Malchenko, M. Y. (National Aviation University, 2020)
Settlements with counterparties owed debt directly affects the profitability of the enterprise and determines the discount and credit policy for buyers, ways to accelerate the repayment of debts and reduce bad debts, as well as the choice of conditions of sale that ensure guaranteed flow of funds and is another one of the problems of the enterprise.
Keywords: preparation of applications; acquisition process; client base